Wireless local loop and packet radio technology for developing communities - Saban, Guy (Department of Electrical Engineering, 2024)
In developing countries there is an increasing demand for telecommunications and Internet access. The major hurdle for most of these countries is the lack of adequate telephone network infrastructure. The current problem, especially in Africa, is to find solutitlns which can provide underdeveloped countries with a satisfactory network. This requires 8 relatively fast roll-out at low-cost. Modern wireless system claim to offer quick and easy deployment. However, in many cases the wireless system deployment is delayed because adequate radio plans have to be designed, and they are not optimized for Internet and computer communications. Multihop packet radio can offer computer communication in an easily deployable ad-hoc wireless network which does not require frequency p)auuiug. However, voice traffic is not easily implemented on packet radio networks due to the bursty and delayed traffic characteristcs. A multihop packer radio network is proposed which offers voice and Internet communications.